2021
DOI: 10.1186/s12885-020-07719-y
|View full text |Cite
|
Sign up to set email alerts
|

A population-based analysis of spirometry use and the prevalence of chronic obstructive pulmonary disease in lung cancer

Abstract: Background Chronic obstructive pulmonary disease (COPD) and lung cancer are associated diseases. COPD is underdiagnosed and thus undertreated, but there is limited data on COPD diagnosis in the setting of lung cancer. We assessed the diagnosis of COPD with lung cancer in a large public healthcare system. Methods Anonymous administrative data was acquired from ICES, which links demographics, hospital records, physician billing, and cancer registry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A Canadian public healthcare dataset, including 105,304 patients diagnosed with lung cancer, reported that spirometry was performed in 90.6% of patients with stage I or II lung cancer, whereas in stage III or IV lung cancer, spirometry was performed in only 54.4%. Of the patients with lung cancer, 34.9% had been previously diagnosed with COPD [ 22 ]. However, considering the low rate of spirometry in patients with advanced lung cancer, the actual prevalence of COPD in this patient population is expected to be higher.…”
Section: Pulmonary Outcomesmentioning
confidence: 99%
“…A Canadian public healthcare dataset, including 105,304 patients diagnosed with lung cancer, reported that spirometry was performed in 90.6% of patients with stage I or II lung cancer, whereas in stage III or IV lung cancer, spirometry was performed in only 54.4%. Of the patients with lung cancer, 34.9% had been previously diagnosed with COPD [ 22 ]. However, considering the low rate of spirometry in patients with advanced lung cancer, the actual prevalence of COPD in this patient population is expected to be higher.…”
Section: Pulmonary Outcomesmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is characterized by persistent airway inflammation and fixed airflow obstruction [117]. Over a third of the individuals with lung cancer have a prior diagnosis of COPD [118]. Interstitial pneumonia, a condition that causes progressive fibrosis, is a known risk factor for lung carcinogenesis independent of smoking; epidemiologically, the risk of lung carcinogenesis is 6.42 times in healthy subjects [5].…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…COPD is associated with an increased lung cancer development, which is often underestimated in clinical practice. Studies have reported that 40-70% of lung cancer cases are complicated with COPD ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%